Origin of Distinct Insulating Domains in the Layered Charge Density Wave Material 1T-TaS2 - Yang, Hyungryul; Lee, Byeongin; Bang, Junho; Kim, Sunghun; Wulferding, Dirk; Lee, Sung Hoon; Cho, Doohee (Advanced Science, 2024)
Vertical charge order shapes the electronic properties in layered charge density wave (CDW) materials. Various stacking orders inevitably create nanoscale domains with distinct electronic structures inaccessible to bulk probes. Here, the stacking characteristics of bulk 1T-TaS2 are analyzed using scanning tunneling spectroscopy (STS) and density functional theory (DFT) calculations. It is observed that Mott-insulating domains undergo a transition to band-insulating domains restoring vertical dimerization of the CDWs. Furthermore, STS measurements covering a wide terrace reveal two distinct band insulating domains differentiated by band edge broadening. These DFT calculations reveal that the Mott insulating layers preferably reside on the subsurface, forming broader band edges in the neighboring band insulating layers. Ultimately, buried Mott insulating layers believed to harbor the quantum spin liquid phase are identified. These results resolve persistent issues regarding vertical charge order in 1T-TaS2, providing a new perspective for investigating emergent quantum phenomena in layered CDW materials.
Keywords: Band insulators; Charge-density wave material; Charge-density-waves; Charge-ordering; Density-functional theory calculations; Insulating domains; Insulating layers; Mott insulators; Scanning tunnelling spectroscopy; Stacking order; band insulator; charge density waves; Mott insulator; scanning tunneling microscopy; stacking order